Влияние длительности хранения боеприпасов на баллистические характеристики стрелкового оружия - Анипко, О. Б.; Баулин, Д. С.; Бирюков, И. Ю. (НТУ "ХПИ", 2007)
In clause influence of storage period of ammunition on change of ballistic characteristics small arms is analysed. The model operation of powder charges depending on storage period of ammunition is offered.
Keywords: эксплуатация боевых зарядов; хранение боеприпасов